Kombinasi Arang Kayu dan Jarak Tanam pada Budidaya Kacang Panjang (Vigna unguiculata ssp. sesquipedalis) - Ari Prayitno, Risma; Rahardjo, Tjatur Prijo; Junaidi; Nareswari, Aptika Hana Prastiwi (Universitas Kadiri, 2023)
During the last five years, there has been a significant decline in asparagus bean production, so this commodity has the potential to be developed. The cause of the decrease in asparagus bean production is the use of cultivation techniques that could have been more optimal, especially in terms of spacing. It is necessary to find the best combination of charcoal application and spacing on the growth and yield of asparagus beans (Vigna unguiculata ssp. sesquipedalis) to overcome the problem. The study was conducted in the Faculty of Agriculture, University of Kadiri greenhouse from March to May 2022, using a factorial Randomized Block Design (RBD). The first factor studied was the application of wood charcoal as a mixture of planting media, with three levels of treatment, namely without wood charcoal (B1), 250 g of wood charcoal/plot (B2), and 300 g of wood charcoal/plot (B3). Spacing as the second factor consisted of three levels, namely 20 x 40 cm (S1), 30 x 40 cm (S2), and 40 x 60 cm (S3). Each factor combination was repeated three times, so there were 27 experimental units. The 5% BNT analysis showed an interaction between the treatment of wood charcoal application and plant spacing on the number of asparagus bean leaves at 4 - 6 WAP. The best results were obtained from the combination treatment of 250 g of wood charcoal/plot and a spacing of 40 x 60 cm (B2S3), which produced the best pods on asparagus bean plants. Selama lima tahun terakhir, terjadi penurunan produksi kacang panjang yang signifikan, sehingga komoditas ini memiliki potensi untuk dikembangkan. Penyebab dari penurunan produksi kacang panjang adalah penggunaan teknik budidaya tanaman yang belum optimal, terutama dalam hal pengaturan jarak tanam. Pencarian kombinasi terbaik pemberian arang dan jarak tanam pada pertumbuhan dan hasil kacang panjang (Vigna unguiculata ssp. sesquipedalis) dirasa perlu untuk dilakukan untuk mengatasi masalah. Penelitian dilakukan di greenhouse Fakultas Pertanian Universitas Kadiri pada bulan Maret hingga Mei 2022, dengan menggunakan Rancangan Acak Kelompok (RAK) faktorial. Faktor pertama yang diteliti adalah pemberian arang kayu sebagai campuran media tanam, dengan tiga taraf perlakuan, yaitu tanpa arang kayu (B1), 250 g arang kayu/plot (B2), dan 300 g arang kayu/plot (B3). Jarak tanam sebagai faktor kedua terdiri atas tiga taraf, yaitu 20 x 40 cm (S1), 30 x 40 cm (S2), dan 40 x 60 cm (S3). Setiap kombinasi faktor diulang sebanyak tiga kali, sehingga total terdapat 27 satuan percobaan. Hasil analisis BNT 5% menunjukkan adanya interaksi antara perlakuan pemberian arang kayu dan jarak tanam terhadap jumlah daun kacang panjang pada 4 - 6 MST. Hasil terbaik diperoleh dari kombinasi perlakuan pemberian 250 g arang kayu/plot dan jarak tanam 40 x 60 cm (B2S3), yang menghasilkan polong terbaik pada tanaman kacang panjang.